Konstruksi Keabsahan As-Sulh Dalam Pembagian Waris Melalui Otoritas Kakak Tertua di Desa Jaya Karet Kabupaten Kotawaringin Timur - Radiatus Sholehah; Syaikhu Syaikhu; Rafik Patrajaya (Bajang Institute, 2026)
Islamic inheritance law governs property distribution through faraid provisions understood by the community, yet in Jaya Karet Village, Mentaya Hilir Selatan District, East Kotawaringin Regency, this authority has been taken over by the eldest sibling through two patterns: open deliberation and single authority. This study describes compliance practices toward the eldest sibling in inheritance division and analyzes the legitimacy of both patterns under Islamic inheritance law. The method used is qualitative empirical-legal research with a socio-legal approach, through interviews with heirs and religious figures from several families. Findings show the open deliberation pattern produces sincere compliance grounded in consent (ridha), aligned with sulh and maqashid al-syariah, while the single authority pattern produces superficial compliance driven by reluctance and fear of the “disobedient” stigma, contradicting justice and consent. In conclusion, legitimacy of inheritance division cannot be judged solely from a peaceful outcome but from the openness of the deliberation process. These findings suggest that religious leaders should play a more proactive role in monitoring family deliberations and facilitating written agreements to secure legal certainty for all heirs